2016
DOI: 10.1007/s10552-016-0716-7
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome (PCOS), related symptoms/sequelae, and breast cancer risk in a population-based case–control study

Abstract: Purpose Despite the overlap between the clinical symptoms/sequelae of polycystic ovarian syndrome (PCOS) and many known reproductive risk factors for breast cancer, the relationship between PCOS and breast cancer remains unclear, possibly because of the complex heterogeneity and challenges in diagnosing PCOS over time. We hypothesized that PCOS, specific PCOS-related symptoms/sequelae, or clusters of PCOS-related symptoms/sequelae, may be differentially associated with pre- vs. postmenopausal breast cancer ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 44 publications
0
27
0
2
Order By: Relevance
“…It is possible that the risk reported by Jensen et al was influenced by factors such as higher age at first birth among infertile women. Most previous studies have presented SIRs adjusted only for age and calendar year, which could explain why the risk of breast cancer was found higher in some of them [ 15 , 17 , 28 30 ]. It is reasonable to assume that parity and age at first birth act as mediators rather than confounders in the studied association.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the risk reported by Jensen et al was influenced by factors such as higher age at first birth among infertile women. Most previous studies have presented SIRs adjusted only for age and calendar year, which could explain why the risk of breast cancer was found higher in some of them [ 15 , 17 , 28 30 ]. It is reasonable to assume that parity and age at first birth act as mediators rather than confounders in the studied association.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of publications shows that women with infertility had higher rates of psychiatric disorders and endometrial cancer than the general population [1][2][3][4][5][6][7][8][9][10]. Data is conflicting about whether infertile women are at increased risk for breast cancer and ovarian cancer [7,8,[10][11][12][13][14][15][16][17][18][19][20]. A generalized diagnosis of infertility was not clearly associated with an increased risk of cardiovascular disease or metabolic dysfunction, but women with infertility related to polycystic ovarian syndrome (PCOS) do appear more likely to develop cardioCapsule There is a growing body of literature addressing the impact of female infertility on long-term health.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kim et al identified more than 1,500 women with newly diagnosed in situ or invasive breast cancer and compared them to age-matched controls. 65 Approximately 2.2% of the population reported having a PCOS diagnosis established by a medical professional and the remainder reported no PCOS or were unsure, 96.3 and 1.5%, respectively. The women diagnosed with PCOS were more likely to have used OCs, to have a history of infertility, and to not have regular cycles.…”
Section: Breast Cancermentioning
confidence: 99%